Zooplankton abundance and distribution along the Mawson coast, East Antarctica - Weldrick, Christine K.; Brasier, Madeleine J.; Burns, Alicia; Johnson, Olivia J.; Maschette, Dale (Frontiers in Marine Science, 2024)
The distribution and abundance of zooplankton communities along the Mawson coast, East Antarctica, were investigated during the austral summer of 2021 as part of the TEMPO survey program. Hierarchical clustering revealed three distinct zooplankton communities, each associated with specific environmental gradients. These clusters were characterized by dominant species such as Calanoides acutus and Euphausia superba, which showed strong associations with chlorophyll-a concentration, temperature, and the timing of sea ice melt. Indicator species were identified for each cluster, offering insights into the linkages between community composition and local environmental conditions. Generalized Additive Models (GAMs) were applied to assess the influence of environmental drivers on zooplankton abundance. Chlorophyll-a concentration and the number of days since ice melt emerged as the most significant predictors of total zooplankton abundance. Species-specific models also highlighted temperature and salinity as key factors for the distribution of certain copepods and krill species, underscoring the importance of these variables in shaping zooplankton communities in the Southern Ocean. Our findings enhance the understanding of zooplankton community dynamics in East Antarctica, particularly the role of environmental drivers in structuring species distributions. This study contributes to a growing body of knowledge about how these communities may respond to ongoing climate change, with potential impacts on higher trophic levels and Antarctic food webs. As sea ice dynamics and primary productivity continue to shift, these changes may have cascading effects on Southern Ocean ecosystems, altering nutrient cycling and energy transfer across trophic levels.